The effects of a novel substrate on exercise energetics in elite athletes - Cox, PJ (2013)
The physiological ketosis of starvation makes sound evolutionary sense, as ketone bodies have several thermodynamic advantages over other nutritional substrates, in addition to their actions to conserve protein and glucose stores. Utilising the body’s metabolic responses to ketosis by delivering a novel nutritional source of ketone bodies, the work in this thesis explored the metabolic effects of ketosis on physical performance in humans. First, the pharmacokinetics and dosing requirements for ketone containing drink preparations were characterised in a population of athletes and healthy controls (n = 45). Using endurance exercise as a model of physiologic stress, the functional impact of ketosis during sustained high intensity effort was investigated in high performance athletes (n = 22). It was shown that nutritional ketosis improved performance in 18/22 athletes, who set 14 new best performances during 30 min of rowing. Furthermore, when ketones and glucose were delivered together, cycling performance was improved by 2% (n = 8) following 1.5 hours of fatiguing effort, compared with optimal carbohydrate intake. Blood D-β-hydroxybutyrate reached 3-5 mM following ketone drinks, equivalent to several days of total fasting, but rapidly decreased during exercise. It was found that higher physical workloads correlated with larger decreases in plasma ketone concentration (n = 8), consistent with their oxidation as respiratory fuels. Nutritional ketosis significantly altered fuel metabolism during exercise in elite athletes (n = 10), decreasing peripheral lipolysis, skeletal muscle glycolytic intermediates, blood lactate, and branched chain amino acid release. In conclusion this work suggests a new hierarchy of substrate preference during physical stress, whereby mimicking the physiology of starvation, the energetic consequences of oxidising ketones may significantly enhance athletic performance. The extrapolation of these findings may have therapeutic implications for patient populations where energetic demands are high, and deleterious switches in substrate selection occur.